Exploring Pneumonia Risk Factors in Slum and Non-Slum Areas - Rohimawati, Kartika Dwi; Ardillah, Yustini (Disease Prevention and Public Health Journal, 2021)
Background: Pneumonia remains a health concern that is the most significant contributor to the mortality of children under five years old in the world. The environment and immunization history, exclusive breastfeeding, and nutritional status become risk factors for children's pneumonia. This study aimed to analyze the risk factors for pneumonia in infants in the slum and non-slum areas of Palembang City. Methods: This study used a case-control study design. This population study was all children under five years old who lived in the slum and non-slum Areas of Palembang City. The sample in this study was 84 samples with a ratio of 1:1. Analysis data used univariate and bivariate with chi-square. Results: This study found that in slums showed 5 independent variables related to the incidence of pneumonia in children under five years old, those variables were immunization status (OR=5.2; CI 95%= 1.367-19.774), exclusive breastfeeding (OR= 5.667; CI 95%= 1.411-22.761), humidity (OR= 7.125; CI 95%= 1.309-38.771), ventilation area (OR= 5.2; CI 95%= 1.367-19.774) and occupancy density (OR= 6,9; CI 95%= 1,702-28,026). Whereas in the slums areas, there was a relationship between exclusive breastfeeding (OR= 8; CI 95%= 1.790-35.774), nutritional status(OR= 5.67; CI 95%= 1.411-22.761), humidity (OR= 6.9; CI 95%= 1.702-28.026), and exposure to cigarette smoke (OR= 5.4; CI 95%= 1.226-24.261) with the case of pneumonia in children under five years old. Conclusion: Exclusive breastfeeding and humidity are risk factors for pneumonia in children under five years old in the slum and non-slum areas of Palembang City.